Evaluating Innovation Factors (Authenticity, Packaging, Product and Process) in Traditional Indonesian Handicrafts: A Consumer-Centric Approach to Enhancing Market Competitiveness - Wahyuni, Sri (Manunggal Halim Jaya, 2025)
Traditional handicrafts must embrace innovation to remain competitive against mass-produced machine-made products, which are often more affordable and easily scalable. The primary challenge in this innovation process lies in maintaining authenticity and cultural significance while adapting to contemporary consumer preferences, ensuring that the traditional identity of these crafts is not lost. This study aims to evaluate the implementation of various innovation factors in traditional Indonesian handicrafts, explicitly focusing on Authenticity, Packaging, Product, and Process Innovation. It examines how these factors are integrated into products based on consumer purchasing experiences. Data were collected through a survey using a 5-point Likert scale from 416 respondents who had purchased handicrafts within the past year, employing purposive sampling. The data were analyzed using SPSS and SmartPLS. The results showed that Authenticity Innovation and Packaging Innovation had mean scores below 3.892, indicating that these factors are less adopted or valued in the market and require further improvement. In contrast, Product and Process Innovation scored above average, reflecting a stronger integration into products and a greater focus on innovation in these areas. Unlike previous studies by Shafi et al. (2021), which explored the hypothetical application of consumer acceptance of innovation factors in handicrafts, this study investigates the practical application and consumer experience of innovation adoption in traditional handicraft products that consumers have already purchased. It offers valuable insights into enhancing product offerings and addressing the needs of diverse consumer segments.